ANÁLISIS COMPARATIVO DE SEIS ESPECIES DE CRASULÁCEAS EN TRES SUSTRATOS DERIVADOS DE RESIDUOS ORGÁNICOS - Ramírez Cuenca, Mairalejandra
This study contributes to the generation of knowledge about the development of the crassulacean flora, through the evaluation of the development of six species of this family in substrates (bocaschi, vermicompost and soil prepared in the nursery as a comparative substrate), derived from organic waste, with potential physicochemical characteristics for the development of the crassulacean flora, resulting in different development conditions for each species, established in an experimental design for the application of nine treatments with three repetitions, in order to determine the effectiveness of rooting and the development of the species. evaluated. The information was collected in the field, it was processed in the Design Expert software. Concluding that the substrates obtained from organic waste are a good option for the reproduction of crasulaceae, taking into account that each species has its own substrate requirements, which when combined with granite and sand largely determine the rooting and development of plants